2002
DOI: 10.1038/sj.gt.3301616
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral gene therapy of malignant brain tumor in a rat model with angiostatin delivered by adeno-associated viral (AAV) vector

Abstract: We have utilized a recombinant adeno-associated viral (AAV)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 45 publications
0
66
0
1
Order By: Relevance
“…To our knowledge, studies of angiostatins in the brain tissue have described only effects of angiostatin-encoding genetic con- structions in animal models of pathologies. Besides, recent studies have suggested that adeno-associated virus angiostatin vector causes markedly smaller tumors with reduced neovascularization and higher apopto tic indices in C6 glioma cells, when they are propa gated intracerebrally and are injected to animals [33]. One of the most significant and novel results of our study is detection of angiostatins in brain tissue, determination of their polypeptide composition and regional distribution.…”
Section: Fig 2 Representative Fluorescence Micrographs Of Plasminogmentioning
confidence: 74%
“…To our knowledge, studies of angiostatins in the brain tissue have described only effects of angiostatin-encoding genetic con- structions in animal models of pathologies. Besides, recent studies have suggested that adeno-associated virus angiostatin vector causes markedly smaller tumors with reduced neovascularization and higher apopto tic indices in C6 glioma cells, when they are propa gated intracerebrally and are injected to animals [33]. One of the most significant and novel results of our study is detection of angiostatins in brain tissue, determination of their polypeptide composition and regional distribution.…”
Section: Fig 2 Representative Fluorescence Micrographs Of Plasminogmentioning
confidence: 74%
“…The use of T cells and macrophages has been extensively studied due to the homing properties of these immune cells. Recently, problems with sustained production of antiangiogenic proteins were overcome by adeno-associated virus-mediated intratumoural delivery (Ma et al, 2002b) or systemic delivery through intramuscular injection of angiostatin for treatment of intracranial tumours (Ma et al, 2002a) or endostatin for treatment of ovarian carcinoma (Subramanian et al, 2006). Long-term survival of mice with intracranial human glioblastoma was also seen when the Sleeping Beauty transposon system was used for the transfer of a gene encoding soluble vascular endothelial growth factor receptor or a fusion gene for angiostatin -endostatin (Ohlfest et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, when coupled to a strong promoter like the hybrid CMV enhancer/chicken b-actin (CAG) promoter used in this study, it is capable of delivering high levels of transgene expression in a wide variety of cell types. For these reasons, AAV carrying therapeutic genes like angiostatin, 31,32 herpes simplex virus thymidine kinase (HSV-tK), 33,34 and interleukin-2 (IL-2) 35 have been employed in the treatment of malignant gliomas with varying degree of success. In the present study, we demonstrated that intratumoral delivery of rAAVhTERTC27, but not rAAV-EGFP, potently inhibits the growth of the glioblastoma cells by more than 80% at 5 weeks post-treatment and significantly prolongs the median survival time of the treated mice by approximately twofold.…”
Section: Raav-htertc27 Treatment Induces Differential Expression Of Gmentioning
confidence: 99%